Football (Soccer) refereeing and cardiovascular health: A scoping review - Toby M Plasto; Geoffrey H Tofler; Tom Buckley (PLoS ONE, 2026)
Background Physical and psychological stress can precipitate Acute Coronary Syndrome (ACS) events. Football (soccer) is a popular sport globally, with referees covering significant distances, often at high-intensity during a match, and facing potentially intense psychological stress from high-stakes decision-making and potential verbal abuse from players and spectators. The aim of this scoping review was to identify what is known about the cardiovascular health and risk of acute cardiac events in referees during football matches. Methods A librarian-assisted search of six databases was completed, with publications written in English or with English translation available included. The PRISMA checklist was utilised and data were extracted from publications to form both descriptive and thematic analyses. Results Analysis of the publications identified five key themes: 1) the cardiovascular risk factors profile of football referees (prevalence of hypertension, dyslipidaemia and diabetes), 2) psychological stress and abuse experienced by referees (both verbal and physical abuse are reported at all levels of football, contributing to stress, anxiety, and anger), 3) physical intensity and activity levels of football referees (distance covered per match), 4) physiological aspects of football refereeing and 5) cardiac events on the football field (referees are rarely involved in providing CPR). Conclusions Evidence indicates that football referees face significant cardiovascular demands and psychological stress, along with a vulnerability to physical abuse, yet there is a lack of research on educational interventions to promote their cardiovascular health. Additionally, referees may act as first responders during ACS events, highlighting the necessity for them to be knowledgeable about relevant symptoms and trained for effective response.